Health behaviors of young people during late adolescence - Stępień, Renata; Wiraszka, Grażyna; Dajer, Anna (Nursing in the 21st Century, 2015)
HEALTH BEHAVIORS OF YOUNG PEOPLE DURING LATE ADOLESCENCE Aim. The objective of the study was to analyze health behaviors in young people during late adolescence with regard to the dietary habits, physical activity, rest and stress. Material and methods. The study was conducted in a group of 258 high school students aged 18-19 years. The study was conducted in April 2015 in the town of Końskie within the Świętokrzyskie Province. The study was conducted using the diagnostic survey method. Results. As shown by the study, more than one half of the students declared non-adherence to healthy lifestyle principles (n=136; 53%). More than 63% of students slept less than 7 hours per every 24 hours. The young people preferred passive leisure pastimes; only about 13% of responders practiced sports every day. High stress levels were reported by every third student (34.1%). The most common form of stress-relieving activity consisted in video gaming (35%). Two factors that significantly differentiated health behaviors in adolescents were gender and place of residence. Conclusion. Most young people are satisfied with their health and most commonly consider it to be good. The physical aspects of the lifestyle of subjects requires monitoring and improvement, which particularly pertains to physical activity, changing dietary habits and leisure. The young people declared high levels of stress that was relieved mainly by escaping into the realm of video games.